Lost in Regulation: Nord Stream 2 and the Limits of the European Commission’s Geo-Economic Power - de Jong, Moniek; Van de Graaf, Thijs (Journal of European Integration, 2021)
Scholars of the EU’s external relations have long debated the question which ‘power’ the EU represents. When it comes to the EU’s external energy relations, there is a convergence of views that the Commission has begun to assert its regulatory power beyond its own borders. Yet, few scholars have attempted to open the black box of this ‘liberal mercantilist’ model. This paper aims to fill that gap by process tracing and explaining the Commission’s attempts to stymie the Nord Stream 2 gas pipeline project. Our analysis shows that the Commission has attempted, largely in vein, to achieve geopolitical ends through legal means. We find that this outcome can be explained through the lens of new integration theories. Our analysis illustrates both the limits of the Commission’s regulatory toolbox and its efforts to broaden its mandate and strengthen its regulatory powers.
Created from Fastlane, Scopus look-up
Keywords: European Commission; European integration; Gas Directive; International energy governance; new intergovernmentalism